Structural optimization and simulation of piezoelectric- piezoresistive coupled MEMS steady-state electric field sensor - Liu, Guote; Ye, Yuanhao; Luo, Bing; Gu, Yu; Zheng, Weijia; Chen, Sijun (Frontiers in Energy Research, 2023)
Aiming at the problems of large size, high energy consumption, and difficult operation and maintenance of the existing electric field measurement sensors in the power system, this paper uses the finite element method to build a MEMS (micro electro mechanical systems) micro electric field measurement sensor model based on piezoelectric-piezoresistive coupled. The steady-state characteristics of piezoelectric materials and semiconductor films of different sizes for micro electric field sensors were analyzed, and the optimization scheme of piezoelectric materials and semiconductor films for MEMS micro electric field sensors was designed, and the optimal doping area for placing varistor patches was determined, so as to Improve the feasibility of the sensor for electric field measurement. The research results show that when the piezoelectric material of the electric field sensor has a side length of 400μm and a thickness of 350μm, the thickness of the semiconductor film is 20μm and the side length of the semiconductor film is 500μm, the steady-state electric field can be effectively measured. The research results will provide some theoretical reference for the parameter optimization of MEMS electric field sensor.